Herbicidal effects on nodulation, yield and weed control in soybean (Glycine max) - BILLORE, S D; JOSHI, O P; RAMESH, A (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted in rainy season (kharif) 1997 to evaluate the effect of different herbicides onnodulation, dry matter production and weed biomass in soybean. The study revealed that the maximal and minimalnodule number and their dry weight were associated with application of imazethapyr and 2 hand weedings. Applicationof lactofen as post-emergence did not cause appreciable variation in weed load. Increased dry biomass was observedwith application of propaquizafop @ 75 g ai/ha and lactofen @ 90 g ai/ha. Application of imazethapyr @ 100 g ai/haresulted in maximum yield and was at par with lower dose of imazethapyr, 2 hand weedings and trifluralin.